Kandungan pemikiran dalam qs. Al-'alaq (96): 1-5 tafsir Al-Mishbah dan AlʻAzim (Tinjauan Pendidikan Islam) - Muslimah, Defy Catur, Dra. Mahasri Shobahiya, M.Ag (2017)
Islamic attention to science especially in Islamic education is very large and important. One of the content of thought in QS. Al-'Alaq (96): 1-5 in the Tafsir Al-Mishbah and Al-ʻAẓīm discussed here is the Islamic education. Thus, the problem formulation in this study is "What is the content of thinking in QS. Al-'Alaq (96): 1-5 according to the Tafsir Al-Mishbah and Al-ʻAẓīm (on Islamic education)? ", with the aim of describing the content of thought in the QS. Al-'Alaq (96): 1-5 according to the Tafsir Al-Mishbah and Al-ʻAẓīm (on Islamic education). This research is a library one with qualitative descriptive approach. The primary data sources in this study are the Tafsir Al-Mishbah and Al-ʻAẓīm, and secondary data sources of books or research related to this research. A data collection technique used is documentation one, and a data analysis method used is comparative (comparing). The study has found that the content of thought in QS. Al-'Alaq (96): 1-5 according to the Tafsir Al-Mishbah and Al-ʻAẓīm are: first, the educational values of Islam: (1) the educational value of faith; (2) the value of shari'ah education; (3) the value of moral education; and (4) the value of intellectual education. The equation of Islamic educational values between the Tafsir Al-Mishbah and Al-ʻAẓīm are that both have the values of aqidah education, morals and reason. In addition, there is also a difference, namely in the value of shari'ah education founded in the Tafsir Al-Mishbah and not-founded in the Tafsir Al-ʻAẓīm. Another difference is seen in terms of interpretation, Al-Mishbah interprets word by word, while Al-ʻAẓīm interprets verse by verse. Second, the scope of Islamic education. The equation of the scope of Islamic education between the Tafsir Al-Mishbah and Al-ʻAẓīm, are in terms of: (1) the purpose of Islamic education; (2) educators; (3) learners; (4) materials; and (5) Islamic educational model. In addition, there are also differences, namely related to: (1) Islamic education model, according to Al-Misbah there is a model of social interaction, whereas according to Al-ʻAẓīm, there is a personal model. Related to the model, it can not be separated from the method of Islamic education, according to Al-Mishbah there are methods of parable, whereas in Al-ʻAẓīm did not exist; and (2) educational tool, according to Al-Mishbah, is by using tools or without tools, whereas according to Al-ʻAẓīm, the educational tool in the form of writing material.